Gestational Day-Dependent Expression of Interleukin-10 and Tumor Necrosis Factor-alpha in Porphyromonas gingivalis-infected Pregnant Rats - Banun Kusumawardani; Marsetyawan HNE Soesatyo; Djaswadi Dasuki; Widya Asmara (Faculty of Dentistry, Universitas Indonesia, 2014)
<!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Fetal growth restriction remains a major cause of neonatal morbidity and mortality. Porphyromonas gingivaliscan induce placental inflammatory response resulting in fetal growth restriction. Objective: This study aimed to evaluate the potential utility of the pro-inflammatory cytokine TNF-α and anti-inflammatory cytokine IL-10 in rat placental tissues to understand whether these events were causally related. Methods: Female rats were infected with live-Porphyromonas gingivalis at concentration of 2x109 cells/ml into subgingival sulcus area of the maxillary first molar before and/or during pregnancy. They were sacrificed on gestational day (GD)-14 and GD20. The expression of TNF-α and IL-10 in macrophages and trophoblast cells were detected by immunohistochemistry. Results: A higher expression of TNF-α was found in spongiotrophoblast of the Pg-BD group on GD14 (6.30±1.16), and in trophoblastic giant cells of Pg-D group on GD20 (5.50±1.35). Furthermore, a higher expression of IL-10 was found in trophoblastic giant cells of the Pg-BD group on GD14 (4.50±1.51) and in syncytiotrophoblasts of Pg-BD group on GD20 (8.70±2.67). Conclusion: The expression of TNF-α on GD14 and GD20 were accompanied by increased expression of IL-10. The placental pathologic conditions induced by Porphyromonas gingivalis can be inhibited by elevated expression of IL-10 in macrophages and trophoblast cells. DOI: 10.14693/jdi.v20i3.199